Urban health combating disparities with local data - Whitman, Steven; Shah, Ami M.; Benjamins, Maureen R. (New York ; Oxford : Oxford University Press, 2011)
This book describes how a landmark health survey in Chicago generated dramatic data that are allowing investigators throughout the city to move from data to action and from observation to intervention.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Urban health -- Illinois -- Chicago; Health surveys -- Illinois -- Chicago; Community health services -- Illinois -- Chicago; Health surveys -- Illinois -- Chicago